Role of Kinematics Assessment and Multimodal Sensorimotor Training for Motion Deficits in Breast Cancer Chemotherapy-Induced Polyneuropathy: A Perspective on Virtual Reality Avatars - Axenie, Cristian; Kurz, Daria (Frontiers in Oncology, 2020)
Chemotherapy-induced polyneuropathy (CIPN), one of the most disabling side effects of chemotherapeutic drugs, is a severe problem in breast cancer therapy leading to dose reduction, delay or discontinuation. The reversibility of CIPN is of increasing importance since active chemotherapies prolong survival. Clinical assessment tools show that patients experiencing sensorimotor CIPN symptoms not only have to deal with the reduction in their autonomy and quality of life, but CIPN has become a crucial therapy limiting factor. The occurrence of CIPN presents a diagnostic dilemma and, up to now, approved and effective treatment options are lacking. Complementary, non-opioid therapies are sought for both prevention and management of CIPN. In this perspective, we explore the potential that digital interventions have for sensorimotor CIPN rehabilitation in breast cancer patients. Our primary goal is to emphasize the benefits and impact that Virtual Reality (VR) avatars and Machine Learning have in combination in a digital intervention aiming at 1) assessing the complete kinematics of deficits through learning underlying patient sensorimotor parameters, and 2) parametrize a multimodal VR simulation to drive personalized deficit compensation. We support our perspective by evaluating sensorimotor effects of chemotherapy, the metrics to assess sensorimotor deficits, and relevant clinical studies. We subsequently analyse the neurological substrate of VR sensorimotor rehabilitation, with multisensory integration acting as a key element. Finally, we propose a closed-loop patient-centred design recommendation for CIPN sensorimotor rehabilitation. Our aim is to provoke the scientific community towards the development and use of such digital interventions for more efficient and targeted rehabilitation.